The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1182/blood-2011-05-353482
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of fibrinolysis by S100A10 in vivo

Abstract: Endothelial cells form the inner lining of vascular networks and maintain blood fluidity by inhibiting blood coagulation and promoting blood clot dissolution (fibrinolysis). Plasmin, the primary fibrinolytic enzyme, is generated by the cleavage of the plasma protein, plasminogen, by its activator, tissue plasminogen activator. This reaction is regulated by plasminogen receptors at the surface of the vascular endothelial cells. Previous studies have identified the plasminogen receptor protein S100A10 as a key r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
115
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(124 citation statements)
references
References 45 publications
9
115
0
Order By: Relevance
“…Follow-up studies examining AnxA2 -/-mice in the carotid artery injury model revealed that besides Src kinase, protein kinase C (PKC) was also required for AnxA2/p11 translocation to the cell surface . Further supporting a role for AnxA2/p11 in fibrinolysis, de-regulated fibrinolysis was also evident in p11 KO mice (Surette et al, 2011).…”
Section: Anxa2 Ko Micementioning
confidence: 83%
“…Follow-up studies examining AnxA2 -/-mice in the carotid artery injury model revealed that besides Src kinase, protein kinase C (PKC) was also required for AnxA2/p11 translocation to the cell surface . Further supporting a role for AnxA2/p11 in fibrinolysis, de-regulated fibrinolysis was also evident in p11 KO mice (Surette et al, 2011).…”
Section: Anxa2 Ko Micementioning
confidence: 83%
“…Supporting the requirement for both proteins, mice deficient in either annexin a2 or p11 protein expression have defective fibrin clearance and angiogenesis (29,37). However, it is important to note that annexin a2 protein expression has been shown to regulate the stability of p11 protein in vitro (20,38,39) and in vivo (19), therefore making it difficult to interpret which protein deficit was responsible for the observed phenotype.…”
mentioning
confidence: 96%
“…Interestingly, TIME cells depleted of ANXA2 showed similar losses in plasminogen binding and plasmin generation as the S100A10-depleted TIME cells. 41 It has been shown that ANXA2 stabilizes the levels of S100A10 protein and that, consequently, ANXA2 knockdown cells are also depleted of S100A10. 45,67,80,81 Because the decrease in plasminogen binding and plasmin generation were similar for TIME cells depleted of S100A10 compared with TIME cells depleted of both ANXA2 and S100A10, we concluded that the loss of cell surface ANXA2 does not affect plasminogen binding or plasmin generation in these endothelial cells.…”
mentioning
confidence: 99%
“…For instance, we can easily distinguish between WT ANXA2 and plasmin-proteolyzed ANXA2 (Ala-28-Asp-338, a loss of 27 residues) by Western blotting. 41 Analysis of cell surface ANXA2 has identified intact ANXA2 but failed to observe any truncated ANXA2. 37,39,40 Recently, we examined the molecular weight forms of ANXA2 at the endothelial cell surface by Western blotting.…”
mentioning
confidence: 99%